TECHNOLOGIES OF USE OF PEOPLE'S PEDAGOGY IN SPIRITUAL AND MORAL EDUCATION OF STUDENTS - Ummatkulovna, Khudoikulova Zarifa (International Journal of Psychosocial Rehabilitation, 2020)
The article deals with the technology of using folk pedagogy in the spiritual and moral education of students. At the same time, the results of experimental work on the role of folk pedagogy in the spiritual and moral education of students in the field of labor education are analyzed. A model of spiritual and moral education of students has been created. conclusions and recommendations on the technology of spiritual and moral education of students. The spiritual and moral qualities of the future specialist are a professional quality and are formed in the pedagogical process carried out in higher education institutions. At the same time, it has been proved that the effective use of knowledge, skills and abilities in folk pedagogy with professional training in the field of labor education is important and relevant.